2020
DOI: 10.1002/1878-0261.12689
|View full text |Cite
|
Sign up to set email alerts
|

Histone methyltransferase SETD1A interacts with HIF1α to enhance glycolysis and promote cancer progression in gastric cancer

Abstract: Growing tumors alter their metabolic profiles to support the increased cell proliferation. SETD1A, a histone lysine methyltransferase which specifically methylates H3K4, plays important roles in both normal cell and cancer cell functions. However, the function of SETD1A in gastric cancer (GC) progression and its role in GC metabolic reprogramming are still largely unknown. In the current study, we discovered that the expression of SETD1A was higher in GC tumor specimens compared to surrounding nontumor tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…In our previous study, we discovered that histone methyltransferase SETD1A interacts with HIF1α to enhance glycolysis and promote GC progression [30]. Therefore, we believe that YTHDF2 has an important role in GC.…”
Section: Discussionmentioning
confidence: 95%
“…In our previous study, we discovered that histone methyltransferase SETD1A interacts with HIF1α to enhance glycolysis and promote GC progression [30]. Therefore, we believe that YTHDF2 has an important role in GC.…”
Section: Discussionmentioning
confidence: 95%
“…Gastric cancer dataset was obtained from The Cancer Genome Atlas (TCGA). The SCARA5 expression and association were examined by Gene Expression Profiling Interactive Analysis (GEPIA) ( http://gepia.cancer-pku.cn/ ) 12 and UALCAN dataset ( http://ualcan.path.uab.edu/ ). Overall survival of GC patients was detected by Kaplan-Meier Plotter (http://kmplot.…”
Section: Methodsmentioning
confidence: 99%
“…Overall survival of GC patients was detected by Kaplan-Meier Plotter (http://kmplot. com/analysis/) 12 . The GEO dataset included GSE14210, GSE15459, GSE22377, GSE29272, GSE51105.…”
Section: Methodsmentioning
confidence: 99%
“…The Western blot assay was performed as previously ( Wu et al, 2020a , b ). In brief, cells were lysed by RIPA buffer and centrifuged, the supernatants were collected for Western blot, and 10∼30 μg proteins were separated and transferred onto PVDF membranes.…”
Section: Methodsmentioning
confidence: 99%
“…SETD1A, which methylates H3K4, plays key roles in cancer progression, including in colorectal and breast cancers ( Shilatifard, 2012 ; Salz et al, 2014 , 2015 ; Tajima et al, 2015 ), and sorafenib resistance ( Wu et al, 2020a ). Our previous study reported that SETD1A promotes GC tumorigenesis by enhancing glycolysis ( Wu et al, 2020b ). However, whether SETD1A promotes GC metastasis remains unknown.…”
Section: Introductionmentioning
confidence: 99%